PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BIOLOGI KELAS XI-IPA DI SMA NEGERI 1 ULUSUSUA - Putri Handayani Giawa (TUNAS : Jurnal Pendidikan Biologi, 2024)
This research aims to determine the application of the flipped classroom learning model to improve student learning outcomes in biology learning in class XI-IPA at SMA Negeri 1 Ulususua. Based on the results of research carried out by researchers regarding improving the quality and cognitive learning outcomes of students through the flipped classroom learning model for Biology Science subjects in class XI, it can be concluded that student learning outcomes have increased from cycle I to cycle II. This is based on data from the results of observations of student and researcher activities. The percentage of observations of student and researcher activities in the first cycle was in the sufficient category, while observations of student and researcher activities in the second cycle experienced an increase, namely being in the very good category. Based on the results of these observations, it can be concluded that the learning model using the flipped classroom learning model can improve the quality of learning and students' cognitive learning outcomes. Suggestions for teachers to make the flipped classroom learning model an alternative that is worth considering in learning. Future researchers hope that this research can become a relevant reference with a wider scope.